Analysis of Hate Speech in Instagram Social Media Celebrity Indonesia Chandrika Sari Jusman - Merlyn Titahena; Prihadi (Britain International for Academic Research (BIAR) Publisher, 2023)
The development of information and communication technology today makes it easier for someone to interact with other people. The current interaction process can be done through social media. But what has been found now is that social media is also abused by irresponsible parties by spreading hate speech. This study aims to describe the form and meaning of hate speech against Selebgram Chandrika Sari Jusman on Instagram social media. This research is a descriptive-qualitative research. The data collection method used is the method of observing and noting. The data analysis method in this study refers to the Miles and Huberman model which includes data reduction, data presentation and drawing conclusions. The results of the study showed that there were 25 assertive utterances, 15 directive utterances, 50 expressive utterances, and 10 declarative utterances. The most commonly found utterances are expressive utterances.